Pengembangan Kompetensi Mahasiswa dalam Berwirausaha melalui Workshop Pemasaran Digital Berbasis AI - Suseno, Pangki (-, 2025)
The purpose of this community service activity is to improve understanding and enhance students' AI-based marketing skills. On March 22, 2025, the activity was conducted through lectures and practical sessions, along with an evaluation of students' understanding before and after the workshop. Topics covered in the workshop included understanding AI for digital marketing, market research and buyer persona analysis using AI, creating text and video content with AI, campaign optimization and data analysis with AI, and practical digital marketing with AI. The results of this PKM activity indicate that students understood the installation process; 57.9% of participants understood how to use the POM-QM software. Additionally, 70% of students understood AI for digital marketing. The evaluation results also revealed that the training helped students address product marketing issues effectively and efficiently.